The Development of Biology Practicum Guidebook using Scientific Approach Based on Guided Inquiry for Senior High School Students - Azizah, Nurul; Wardani, Imaniah Bazlina; Fauzi, Ilham Saiful (META: Journal of Science and Technological Education, 2024)
The guided inquiry practicum guidebook is an effective tool for actively engaging students in the learning process. It was observed that biology teachers and students at MAN 1 Banyuwangi solely rely on textbooks and other basic media for the learning process. This study aims to provide a comprehensive description of the validity, student responses, and usefulness of producing a biology practicum guidebook using a Guided Inquiry based Scientific approach for class XI Science students at MAN 1 Banyuwangi. The research and development method used is the ADDIE approach. The research was carried out at MAN 1 Banyuwangi, using interview guidelines and questionnaire sheets as data collection instruments. This research utilized one material expert validator, one media expert validator, one language expert validator, one assessment expert validator, and one Biology Teacher. This validation is conducted to assess the authenticity of the educational resource. The research findings indicate that the average validation results from material experts achieved a percentage of 84.43% with highly valid criteria. Similarly, the average validation results from media experts attained a percentage of 95.10% with highly valid criteria. The linguist validation yielded a percentage of 90.27%, the evaluation expert validation achieved a percentage of 95.10%, and the teacher validation obtained a percentage of 97.5%, all with highly valid criteria. Furthermore, the average student response questionnaire yielded a result of 91% with excellent criteria. According to the findings of this study, it can be inferred that the product in the form of a practical guidebook is classified as highly valid and highly practical.